2020
DOI: 10.1101/2020.02.18.954594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeking Candidate Molecules as Prognostic Healing Markers in Chronic Venous Ulcers

Abstract: Faculdade de Medicina de Botucatu, FMB) for making available all the resources and equipment that contributed to this work. We acknowledge the Mass Spectrometry Laboratory at the Brazilian Biosciences National Laboratory, CNPEM, Campinas, SP, Brazil, for its support with the mass spectrometric analysis. 3 ABSTRACT 1 Seeking and identifying biomarker molecules in inflammatory exudate of chronic 2 venous ulcers (CVUs) can aid health professionals in the healing prognosis. The 3 therapeutic failure or cure is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This prognosis is only possible by evaluating the expression of the proteins isolated in the exudates by means of shotgun label-free strategy. Those easily healed express mainly complement C3 and ceruloplasmin, whereas those that are difficult to heal express apoliproteína a1 and neutrophil defensina-1 [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prognosis is only possible by evaluating the expression of the proteins isolated in the exudates by means of shotgun label-free strategy. Those easily healed express mainly complement C3 and ceruloplasmin, whereas those that are difficult to heal express apoliproteína a1 and neutrophil defensina-1 [69].…”
Section: Discussionmentioning
confidence: 99%
“…In another work, Cavassan et al [69] identified differentially expressed proteins in the inflammatory exudate of VUs and correlated them with the ease or difficulty of healing. The same 37 ulcers indicated in the 2019 study [68] were monitored for 90 days.…”
Section: Advances In the Diagnostic And/or Prognostic Approach Toward Venous Ulcers By Means Of Proteomic Strategiesmentioning
confidence: 99%